2010
DOI: 10.1016/j.jacc.2009.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Therapy and Heparin “Bridging” Significantly Increase the Risk of Bleeding Complications After Pacemaker or Implantable Cardioverter-Defibrillator Device Implantation

Abstract: Dual antiplatelet therapy and periprocedural heparin significantly increase the risk of bleeding complications at the time of pacemaker or ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 22 publications
(14 reference statements)
11
89
0
Order By: Relevance
“…However, a previous study found a similar prevalence of CD (56%) among PMPs in a neighbor Brazilian state [7]. Chagas' cardiomyopathy is characterized by HF, sudden death, arrhythmias, and thromboembolic events [3]. Although we observed a significantly increased CV mortality rate among PMPs with CD, after adjustment for the presence of HF symptoms, there was no difference in CV mortality.…”
Section: Recorded Parameterssupporting
confidence: 45%
See 3 more Smart Citations
“…However, a previous study found a similar prevalence of CD (56%) among PMPs in a neighbor Brazilian state [7]. Chagas' cardiomyopathy is characterized by HF, sudden death, arrhythmias, and thromboembolic events [3]. Although we observed a significantly increased CV mortality rate among PMPs with CD, after adjustment for the presence of HF symptoms, there was no difference in CV mortality.…”
Section: Recorded Parameterssupporting
confidence: 45%
“…The state of Goias, in central Brazil, has a CD prevalence higher than national average [3,6]. Furthermore, most of our patients lived in rural areas since an early age and were subsequently exposed to the CD vector.…”
Section: Recorded Parametersmentioning
confidence: 88%
See 2 more Smart Citations
“…Tompkins et al reported that dual antiplatelet therapy in patients undergoing pacemaker implantation significantly increased frequency and severity of hemorrhagic complications, compared with the use of aspirin alone [29]. Other authors found no increased risk of bleeding complication in patients receiving clopidogrel or DAPT [30,31].…”
Section: Antithrombotic Therapy In Patients Undergoing Cardiac Rhythmmentioning
confidence: 99%